Pemikiran Anre Gurutta Muhammad Abduh Pabadja Tentang Lailatul Qadr Dalam Rekaman Suara Di Radio Mesra Pare-Pare - Mariani Idris; Achmad Abubakar; Muhammad Irham; Panggih Widodo; Yusuf Rahim (Kopertais Wilayah XV Lampung, 2022)
Lailatul Qadr is still an unsolved mystery, considering that there are many different opinions related to the decline of Lailatul Qadar. There are some who say that Lailatul Qadar descended at the beginning of Ramadan; there are also those who say Lailatul Qadar is in the last ten days of Ramadan; and some even argue that Lailatul Qadar was revealed on odd days in the last ten days of Ramadan. This study aims to understand the interpretations of the Koran originating from Sulawesi, one of which is discussed in this research, namely Anre Gurutta Muhammad Abduh Pabadja in his book entitled al-Quran al-Karim al-lughah al-Bugisiyyah through audio recordings that can be obtained from Radi Mesra Pare-pare . The method used in this research is library research using a qualitative descriptive analytical approach. The results in the explanation of this study indicate that Lailatur Qadr is a night of glory, which is filled with many blessings in it and can erase all sins that have been committed in the past. So it can be concluded that the night of Lailatul Qadr is a night full of blessings. Blessings can be felt when one has strong faith and only hopes for Allah's blessing.